KINETIC ENERGY OF THE SWINGING SEPARATOR DRIVEN BY A LINEAR ELECTRIC MOTOR - Nafikov, Marat; Aipov, Rustam; Akchurin, Salavat; Akhmarov, Ramzid; Akhmetyanov, Ilshat; Zagirov, Ilnur (Journal of Applied Engineering Science, 2020)
The goal of the given study is to develop a gearless mechanism driven by a linear electric motor that can reproduce and adjust sieve oscillation modes of large amplitude (more than 0.01 m) and low frequency (less than 10-12 rad/s). The authors developed a test sample of a swinging separator driven by a linear electric motor and its kinematic scheme. There is a design scheme used to determine motion geometric and kinematic characteristics of the drive mechanism units as a function of the generalized coordinate hh – the stroke of a rotor relative to a stator in the linear electric motor dh/dt. The paper provides kinetic energy expressions that are convenient for further development of a mathematical model for the mechanism movement based on Lagrange equations of the second kind. Most mechanical and technical systems are studied with Lagrange equations being the scientific basis for the analysis and synthesis of a wide variety of machines and devices. This paper relies on the Lagrange equations to give a mathematical description of the sieves’ movement in a grain cleaner. The paper presents kinetic energy expressions for the studied mechanism that are convenient for further development of a mathematical model of its motion based on Lagrange equations of the second kind. The results of the performed analytical studies can be used not only in the design of drive mechanisms for swinging sieves, but also in the design, upgrade and optimization of different industrial and agricultural machines driven by linear asynchronous motors.